Investigating the use of duration‐based windows and estimation by analogy for COCOMO. Issue 10 (29th May 2019) - Nguyen, Vu; Huynh, Thuy; Boehm, Barry; Huang, LiGuo; Truong, Thong
Abstract: In model‐based software estimation, using the right training data is a key contributor for making accurate predictions, which is crucial for the success of software projects. This study investigates the use of duration‐based windows and estimation by analogy to calibrate COCOMO and assess their estimation performance. We compare these approaches as well as the use of all available historical data using the COCOMO data set of 341 projects and NASA data set of 93 projects. The results show that timing information exists in the data sets affecting estimation accuracy. Given sufficient data for calibration, using recently completed projects within short durations generates more accurate estimates than retaining all historical data or using k ‐nearest neighbors based on estimation by analogy. More training data spanning a long period of time may not lead to improved estimation accuracy. This study offers evidence to support the use of projects completed within recent years for training estimation models.